Fire-retardant polyester composites from recycled polyethylene terephthalate (PET) wastes reinforced with coconut fibre - Nurul Munirah Abdullah; Ishak Ahmad (Universiti Kebangsaan Malaysia, 2013)
Coconut fibre reinforced composite was prepared by blending unsaturated polyester resin (UPR) from waste PET with 0.3 v% of coconut fibre. The coconut fibres were pre-treated with sodium hydroxide followed by silane prior to inclusion into the UPR. The untreated coconut fibres reinforced composite were used as a control. Dricon® as a phosphate type of flame retardant was then added to the composite to reduce the flammability of the composite. The amount of Dricon® was varied from 0 to 10 wt% of the overall mass of resin. The burning properties and limiting oxygen index (LOI) of the treated and untreated composites increased with the addition of Dricon®. The tensile strength and modulus of both composites were also increased with the addition of Dricon®. The treated fibre composite with 5 wt% Dricon® showed the highest burning time and LOI with the values of 101.5 s and 34 s, respectively. The optimum tensile strength and modulus for treated fibre composite was at 5 wt% Dricon® whereas the untreated fibre composite was at 2.5 wt% loading of Dricon®. Thermogravimetry (TGA) analysis indicated that the degradation temperature increased with the addition of Dricon® up to 5 wt% into UPR/coconut fibre composites. Morphological observations indicated better distribution of Dricon® for treated fibre composite resulted in enhancement of the tensile properties of the treated fibre composite.